The histomorphologic research on reproductive system of Carp (Cyprinus carpio L.) females in Lake Balkhash (Experimental biology, 2017)
This article concerns the histologic research on reproductive system of carp females (Cyprinus carpio L.)  in east and west parts of Lake Balkhash . There were not defined any pathologies which harms the fish productivity or the reserve fund. We can make the concept that the histologic pathologies are the Normal adaptive physiological state for carps.Lake Balkhash is an internal reservoir which has a great number of fishes in comparison with other reservoirs in Kazakhstan, and it contains 20 % of yearlong fishing rate at all in our country.However if the damages of a condition of simulated manifolding of fish, and pirate catching of fishes during the spawning period, including if the distortion of females proceeds during spawning period will not stop, then in the next years the quantity of productive species of fish will decrease sharply.The gametogenesis (a spermatogenesis and an oogenesis) which is responsible for increase of Fishes, multiplication, for a maturing of genitals, their communication with the world plays a great role. Generally fish production in a reservoir values as the habitat and spawning place of young species, however the poor attention is paid on feature of emergence of reproductive system and its description.The carp belongs to the species of Cyprinus carpio (Linnaeus, 1758). The cyprinids are widely spread in inner water reservoirs and most of them are perfect objects for fish farming. On the other hand, the cyprinids always attract the scientists’ attention by their broad range of morphological and ecological changes, and by broad adaptability at the area edge.Thus the study of carp biology, and  its reproduction are theoretically important as for the productive fishery practice. due to the changes in  contemporary ecological condition of Lake Balkhash, the research of reproductive system of carp females  in reservoirs is the actuality of this scientific work.Histologic researches of gonads of fishes of Lake Balkhash at the tissue level in the modern ecological conditions proved that the periods and stages of development of an oocyte are developing constantlyAs a result of histomorphological research there was defined the resorption of oocyte`s yolks on the vitellogenesis phase, the released follicles, bunch of connecting tissue and atresia, also the continuous process of a vacuolation, the bunch of yolks in egg cell and maturing with yolk granules were normal. However, the resorption of oocytes in the period of a vitellogenezis, the infringement of outer chorion and zona radiate layers, and atresia were defined.There were not revealed dangerous Anomalies in a reproductive system of carp females in the station Ulken. As a result of histomorphological research there was defined the resorption of oocyte`s yolks on the vitellogenesis phase, the released follicles, bunch of connecting tissue and atresia, also the continuous process of a vacuolation, the bunch of yolks in egg cell.There was not revealed dangerous pathologies in a reproductive system of carp females in the station Karzhaubai.  The stages of D1, D2, D3, E1, E2, E3 and maturing with yolk granules were normal. However, the resorption of oocytes in the period of a vitellogenesis , the infringement of outer chorion layers, and atresia were defined.It can be given a good mark on today's state of reproductive system of Carp females in Lake Balkhash. We can make the concept that the microstructural changes are the Normal adaptive physiological state.The changes in tissue cells revealed as a result of a research in female eggs are normal physiological situation. it might be said that the system of female egg manifoldings of highly-productive carps in modern ecological  condition in lake Balkhash is normal.
Keywords: lake Balkhash, Cyprinus carpio L., the reproductive system of females, histomorphologic research.